Subcutaneous emphysema, pneumothorax, pneumomediastinum and acute liver failure in a case of multiple hornet bites - Unnayan Baskota; Jasmine Bajracharya; Nitin Dhamala; Kshitiz Kayastha; Yogendra Poudel; Jayanta Risal (Elsevier, 2023)
Insect bites cause a variety of manifestations ranging from local irritation to systemic effects like anaphylaxis, multi organ failure and death. We present a case of subcutaneous emphysema, pneumothorax, pneumomediastinum and acute liver injury after multiple hornet bites in a pediatric patient. Such cases are rare. However, timely management with emergency needle decompression and compression bandaging followed by intercostal tube decompression and intensive care carried out by a multi-specialty team led by a pediatric surgeon resulted in favorable outcome and good prognosis without complications.